Evaluation of International Technology Transfer for Climate Change Action in Sabah, Malaysia (The Proceedings of The International Conference on Climate Change, 2019)
National Policy on Climate Change of Malaysia stipulates increase of awareness and community participation as one of its strategic thrusts toward which national responses on climate change in all sectors will be directed. Sabah state is the first state in Malaysia to formulate a state-level environmental education policy. In addition, the state is the only state in Malaysia that established a cohesive network of stakeholders concerning environmental education. However, the environmental education in the state had focused on conservation of the biodiversity conservation, etc, and there had been little effort to raise public awareness on climate change and countermeasures against it, such as energy saving measures. On the other hand, in Japan, they have an effective institution at the local administration level for promoting global warming countermeasures, such as the prefectural promotion centres for climate change action, the climate change action officers, etc., which are stipulated in their legal system. Thus, an international collaboration project for three years was planned and implemented to establish a state Centre for Climate Change Action in Sabah, with technical assistance from Japan. With financial assistance from the Environmental Restoration and Conservation Agency (ERCA) of Japan, the Environment Protection Department Sabah (EPD) implemented the project, with technical assistance form he Conference of Earth Environment from Akita (CEEA), an Environmental NGO based in Akita, Japan. This paper evaluates the project, applying the Project Cycle Management (PCM) method, and the DAC five evaluation criteria. Among the five criteria, the Effectiveness of the project was evaluated as extremely high, as the Centre conducted awareness programmes 159 times with 15,728 participants in total, which is far beyond the planned indicators set to verify achievement of the Project Purpose. The Relevance and the Efficiency of the project were evaluated as high, and for the Impacts, the project has exerted some positive impacts. However the Sustainability of the Project is uncertain, as the capacity of the Centre at EPD to maintain and develop the awareness activities even after the project has not been confirmed yet from the institutional, technical and financial points of view.
Keywords: collaboration; climate change; awareness; programme